Benzotriazole Substituted 2-Phenylquinazolines as Anticancer Agents: Synthesis, Screening, Antiproliferative and Tubulin Polymerization Inhibition Activity - Dwivedi, Ashish R.; Rawat, Suraj Singh; Kumar, Vijay; Kumar, Naveen; Kumar, Vinay; Yadav, Ravi Prakash; Baranwal, Somesh; Prasad, Amit; Kumar, Vinod (Current Cancer Drug Targets, 2023)
Aims: Development of anticancer agents targeting tubulin protein. Background: Tubulin protein is being explored as an important target for anticancer drug development. Ligands binding to the colchicine binding site of the tubulin protein act as tubulin polymerization inhibitors and arrest the cell cycle in the G2/M phase. Objective: Synthesis and screening of benzotriazole-substituted 2-phenyl quinazolines as potential anticancer agents. Methods: A series of benzotriazole-substituted quinazoline derivatives have been synthesized and evaluated against human MCF-7 (breast), HeLa (cervical) and HT-29 (colon) cancer cell lines using standard MTT assays. Results: ARV-2 with IC50 values of 3.16 μM, 5.31 μM, 10.6 μM against MCF-7, HELA and HT29 cell lines, respectively displayed the most potent antiproliferative activities in the series while all the compounds were found non-toxic against HEK293 (normal cells). In the mechanistic studies involving cell cycle analysis, apoptosis assay and JC-1 studies, ARV-2 and ARV-3 were found to induce mitochondria-mediated apoptosis. Conclusion: The benzotriazole-substituted 2-phenyl quinazolines have the potential to be developed as potent anticancer agents.
Keywords: anticancer